1996
DOI: 10.1017/s0031182000082019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the transmission of Theileria parva between different instars of Rhipicephalus appendiculatus

Abstract: The transmission of Theileria parva by nymphal and adult Rhipicephalus appendiculatus was compared by the assessment of salivary gland infections in tick batches fed on the same group of infected cattle at the same time. When larval and nymphal R. appendiculatus Muguga ticks were fed concurrently on cattle undergoing acute infection with T. parva Muguga, the resultant nymphae developed a slightly lower prevalence of infection than did the adult ticks. The abundance of infection was 5-20 times higher in the adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Despite it having been reported that the female ticks may play a more important role in transmission than males (Ochanda et al 1996;Salih et al 2005), the development of Theileria parasites in vector ticks depends on several extrinsic and intrinsic factors (Sangwan et al 1989;Sayin et al 2003;Salih et al 2005). Our investigation did not reveal any diVerence between the pathogen-carrying ability of females and males, which is in agreement with the study of Aktas et al (2006).…”
supporting
confidence: 89%
“…Despite it having been reported that the female ticks may play a more important role in transmission than males (Ochanda et al 1996;Salih et al 2005), the development of Theileria parasites in vector ticks depends on several extrinsic and intrinsic factors (Sangwan et al 1989;Sayin et al 2003;Salih et al 2005). Our investigation did not reveal any diVerence between the pathogen-carrying ability of females and males, which is in agreement with the study of Aktas et al (2006).…”
supporting
confidence: 89%
“…Theileria parva infection rates are highest in adult females they are considered the most important stage for acute disease transmission. Nymphal ticks have lower infection levels and are considered important for the transmission of sub clinical disease and as a parasite acquisition stage for adult ticks [28]. The effect of the vaccine focused on the ability of nymph and adult female ticks to successfully feed and for adult females to transmit T. parva .…”
Section: Discussionmentioning
confidence: 99%
“…Its peak of activity in the dry season is correlated with new infections with T. parva (Mulumba et al 2000) and this instar is an effective vector in which the low numbers of theilerial sporoblasts per nymph are probably compensated by the typical 10-fold greater number of nymphs compared to adults infesting cattle (Ochanda et al 1996(Ochanda et al , 2003. If the control of ECf is the priority for strategic control in southern Africa, where there is a distinct seasonal peak of R. appendiculatus nymphs, then this instar needs to be considered.…”
Section: Seasonally Adjusted Timing Of Treatments On Cattlementioning
confidence: 99%